Redo‐surgery after failed colorectal or coloanal anastomosis: Morbidity, mortality and factors predictive of success. A retrospective study of 200 patients. (27th December 2021) - Calmels, Mélanie; Collard, Maxime K.; O'Connell, Lauren; Voron, Thibault; Debove, Clotilde; Chafai, Najim; Parc, Yann; Lefevre, Jérémie H.
Abstract: Aim: In cases of anastomotic failure after colorectal (CRA) or coloanal anastomosis (CAA), revision of the anastomosis is an ambitious surgical option that can be proposed in order to maintain bowel continuity. Our aim was to assess postoperative morbidity, risk of failure and risk factor for failure in patients after CRA or CAA. Methods: All consecutive patients who underwent redo‐CRA/CAA in our institution between 2007–2018 were retrospectively included. The success of redo‐CRA/CAA was defined by the restoration of bowel continuity 12 months after the surgery. Results: Two hundred patients (114 male: 57%) were analyzed. The indication for redo‐CRA/CAA was chronic pelvic infection in 74 patients (37%), recto‐vaginal or urinary fistula in 59 patients (30%), anastomotic stenosis in 36 patients (18%) and redo anastomosis after previous anastomosis takedown in 31 patients (15%). Twenty‐three percent of the patients developed a severe postoperative complication. Anastomotic leakage was diagnosed in 39 patients (20%). One‐year‐success of the redo‐CRA/CAA was obtained in 80% of patients. In multivariate analysis, only obesity was associated with redo‐CRA/CAA failure ( p  = 0.042). We elaborated a pre‐operative predictive score of success using the four variables: male sex, age > 60 years, obesity and history of pelvic radiotherapy. The success of redo‐CRA/CAA was 92%, 86%, 80% and 62% for a preoperative predictive score value of 0, 1, 2 and ≥3, respectively ( p  = 0.010). Conclusions: In case of failure of primary CRA/CAA, bowel continuity can be saved in 4 out of 5 patients by redo‐CRA/CAA despite 23% suffering severe postoperative morbidity.